Dampak Perceived Value dan Perceived Safety Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan Grab Car Sebagai Variabel Intervening - Monix Alfionita Lestari; Diana Aqmala; Handy Nur Cahya; Awanis Linati Haziroh (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to examine the impact of Perceived Value and Perceived Safety on Customer Loyalty through Passenger Satisfaction as an intervening variable in the context of GrabCar services. The study employs path analysis and Sobel test to analyze the direct and indirect relationships between variables. Data was collected through a survey with 107 respondents who are GrabCar users. The results show that Perceived Value and Perceived Safety have a positive and significant effect on Passenger Satisfaction, which in turn positively affects Customer Loyalty. The Sobel test reveals that Passenger Satisfaction serves as a significant intervening variable in the relationship between Perceived Value and Perceived Safety towards customer loyalty. These findings imply that transportation service providers such as GrabCar should focus on enhancing perceived value and safety to improve passenger satisfaction, which ultimately strengthens long-term customer loyalty